Penerapan Inovasi Resource Sharing dalam Mengurangi Tingginya Pengangguran di Provinsi Banten - Bambang Dwi Suseno; Furtasan Ali Yusuf; Syamsul Hidayat; Dewi Surani (Valid: Jurnal Ilmiah, 2021)
The unemployment rate in the August 2019 period in Banten Province was the highest in Indonesia. The ability of Banten Province in preparing employment opportunities is at the lowest level compared to other provinces with the fact that the unemployment rate is 8.11%. This research offers a breakthrough in the form of resource sharing innovation between manufacturing companies and training institutions in the form of models. The research location was conducted in the three largest industrial areas in Banten Province; Serang Regency, Cilegon City and Tangerang Regency. These areas have the highest number of unemployed among other areas in Banten. The data collection method used purposive sampling technique. Where the sample is selected from the apprenticeship population. The questionnaire in this study was distributed to all employees who took 3 in 1 program who had graduated and worked. There were 250 questionnaires distributed to all employees, and 217 employees filled out the questionnaire and it was managed appropriately. Data and hypothesis testing were carried out through the Structural Equation Modeling (SEM) method using the IBM AMOS version 22 application program. The results of this study found that the Skill Development Fund has a significant positive effect on Workforce Competence, the Skill Development Fund has a significant positive effect on the Skill Development Center, the Workforce Competence has a significant positive effect on the Skill Development Center, Workforce Competence has a significant positive effect on Resource Sharing Innovation, Resource Sharing Innovation Has a significant positive effect on Skill Development Center, Skill development center has a significant positive effect on Human Resource Industries Competitiveness, Resource Sharing Innovation has a significant positive effect on Human Resource Industries Competitiveness.